An Introduction to Epigenetics as the Link Between Genotype and Environment: A Personal View. (September 2014) - Van Soom, A; Peelman, L; Holt, WV; Fazeli, A
Contents: Lamarck was one of the first scientists who attempted to explain evolution, and he is especially well known for formulating the concept that acquired characteristics can be transmitted to future generations and may therefore steer evolution. Although Lamarckism fell out of favour soon after the publication of Darwin's work on natural selection and evolution, the concept of transmission of acquired characteristics has recently gained renewed attention and has led to some rethinking of the standard evolutionary model. Epigenetics, or the study of heritable (mitotically and/or meiotically) changes in gene activity that are not brought about by changes in the DNA sequence, can explain some types of ill health in offspring, which have been exposed to stressors during early development, when DNA is most susceptible to such epigenetic influences. In this review, we explain briefly the history of epigenetics and we propose some examples of epigenetic and transgenerational effects demonstrated in humans and animals. Growing evidence is available that the health and phenotype of a given individual is already shaped shortly before and after the time of conception. Some evidence suggests that epigenetic markings, which have been established around conception, can also be transmitted to future generations. This knowledge can possibly be used to revolutionize animal breeding and to increase human and animal health worldwide.